Warming has a greater effect than elevated CO2 on predator–prey interactions in coral reef fish. Issue 1857 (28th June 2017) - Allan, Bridie J. M.; Domenici, Paolo; Watson, Sue Ann; Munday, Philip L.; McCormick, Mark I.
Abstract : Ocean acidification and warming, driven by anthropogenic CO2 emissions, are considered to be among the greatest threats facing marine organisms. While each stressor in isolation has been studied extensively, there has been less focus on their combined effects, which could impact key ecological processes. We tested the independent and combined effects of short-term exposure to elevated CO2 and temperature on the predator–prey interactions of a common pair of coral reef fishes ( Pomacentrus wardi and its predator, Pseudochromis fuscus ). We found that predator success increased following independent exposure to high temperature and elevated CO2 . Overall, high temperature had an overwhelming effect on the escape behaviour of the prey compared with the combined exposure to elevated CO2 and high temperature or the independent effect of elevated CO2 . Exposure to high temperatures led to an increase in attack and predation rates. By contrast, we observed little influence of elevated CO2 on the behaviour of the predator, suggesting that the attack behaviour of P. fuscus was robust to this environmental change. This is the first study to address how the kinematics and swimming performance at the basis of predator–prey interactions may change in response to concurrent exposure to elevated CO2 and high temperatures and represents an important step to forecasting the responses of interacting species to climate change.